Carrier frequency harmonic suppression in dual three‐phase permanent magnet synchronous motor system. Issue 11 (6th June 2019) - Zheng, Boyuan; Xu, Yongxiang; Wang, Guan; Yu, Guodong; Yan, Hao; Wang, Minghui; Zou, Jibin
Abstract : Dual three‐phase permanent magnet synchronous motor (PMSM) is a major area of interest within the field of motors since it inherits the advantages of both the PMSM and multiphase machines. While dual three‐phase PMSM (DTP‐PMSM) system has a more severe carrier frequency harmonic problem due to the low impedance in the harmonic subspace, which will not only decrease the efficiency but also produce the high‐frequency audible noise. This study proposes an improved space vector pulse‐width modulation (SVPWM) strategy by changing the sequence of the pulse‐width modulation wave. The improved SVPWM strategy with a 10 kHz carrier frequency has the same effect as the conventional SVPWM with a 20 kHz carrier frequency, which will significantly decrease the switching loss, lead to lower size of inductance, capacitance and eliminate the high‐frequency audible noise. Three existing mainstream SVPWM strategies in DTP‐PMSM system are introduced and the proposed strategy can be used in them without affecting their original advantages. The switching times are also minimised to reduce the switching loss. The theoretical derivation is proposed to prove the harmonic suppression ability of the proposed SVPWM and the implementation procedure is given then. The simulation and experimental results proved the effectiveness of the strategy.